Utilization of Oil Palm Waste as a Renewable Energy Source: A Current Literature Review - Cecep Ijang Wahyudin; La Oge (Fakultas Teknologi Pertanian Unsultra, 2025)
The palm oil industry is one of Indonesia’s key plantation sectors, generating substantial amounts of both solid and liquid waste. This waste includes empty fruit bunches (EFB), shells, fibers, and palm oil mill effluent (POME). This literature review aims to examine the potential and recent technological advancements in utilizing oil palm waste as an environmentally friendly renewable energy source. A systematic literature review was conducted using journal articles, conference proceedings, and scientific reports published between 2018 and 2024. The findings indicate that oil palm waste can be converted into solid biomass (such as briquettes and pellets), biogas from POME, and raw materials for biodiesel and bioethanol. Technologies employed include anaerobic fermentation, pyrolysis, and gasification. Moreover, the utilization of this waste contributes to greenhouse gas emission reduction and enhances energy efficiency in plantation and processing facilities. However, technical and economic challenges remain major barriers to large-scale development. Collaboration among industry stakeholders, government, and academia is essential for the sustainable optimization of oil palm waste utilization. This study highlights that transforming waste into energy is a strategic step toward national energy resilience and sustainable development.